Cinderella Formula: The Romance Begins - Hirmawan Wijanarka (Journal of Language and Literature, 2022)
As a type of formula fiction, a romance applies a fixed pattern of plot development, including the ending, which is always a happy one: celebrating the unification of the hero and heroine who previously struggled very hard against all obstacles threatening their mutual love. However, it does not mean that discussing the plot of romances is of no use. On the contrary, it is interesting to see how romance writers can create so many possibilities in the structure of the so-called formulaic plot. This study attempts to observe the benefit of characterization in the creation of these various structures of plot development. For this purpose, this study sets up two objectives. Firstly, the study observes the characterization of the hero and heroine as well as the construction of the plots. Secondly, the study points out the significance of characterization in driving the development of the plots. In the light of Cawelty's (1977) perspectives on literary formula and Radway's (1991) ideas about romance, this study concludes that the choice (i.e., the characterization) of "the hero and heroine" proves to be playing an essential role in the plot development. The gaps set between the hero and the heroine make it possible for the writers to develop various complicated plots, focusing on their relationship. Initially, it seems hard to match and unite the hero and the heroine in most romances. This fact, however, is the most crucial part of a romance. The struggles needed to overcome their problems will elicit more emotional conflicts and, thus, create more romantic suspense. The feeling of inferiority, jealousy, fear of losing the partner, and uncertainty about a deeper relationship is likely to occupy the heroine's (and sometimes the hero's) mind. And when they finally successfully overcome these problems, they will feel how great and strong their love is.